Salicaceae of the Kashmir Valley - Javeid, G. N. (Indian Forester, 1972)
The present communication is a systematic account of both exotic and indigenous species of Salicaceae of Kashmir based on personal collection. Keys to the genera and species have been provided to facilitate their identification in the field. Their distribution in the valley and the world, and flowering time has been given. A note on the phytogeography of the valley and its bearing on the probable introduction and distribution of the family has been added.